Pengaruh Price Discount, Store Atmosphere, dan Service Quality terhadap Costumer Loyalty di Critoe Coffee Bandung - Agung Riza Bahari Suryana; Dedy Ansari Harahap; Mochamad Malik Akbar Rohandi (Bandung Conference Series: Business and Management, 2022)
Abstract. Achieving the success of a company is one of them by creating consumer loyalty because it will provide benefits for the company in the long term. This is also what Critoe Coffee wants to achieve, which in recent months has experienced a decline and increase in sales, due to the application of price discounts, store atmosphere and service quality, thus affecting the number of consumers who regularly buy or become loyal consumers. This study aims to determine how the description of discount prices, store atmosphere, service quality and customer loyalty at Critoe Coffee Bandung and to determine the effect of discount prices, store atmosphere, service quality on customer loyalty. This research is a type of descriptive and verification research with quantitative methods. The sampling technique used is non-probability sampling, namely purposive sampling. The population in this study were consumers who had visited and purchased Critoe Coffee products more than twice and received a sample of 396 people. Analysis of the data used is descriptive analysis and verification using multiple linear regression analysis, F test, t test, and coefficient of determination. The results of this study indicate that partially discounted prices have a significant effect on customer loyalty, partially store atmosphere has a significant effect on customer loyalty and service quality has a significant effect on customer loyalty. Simultaneously discounted prices, store atmosphere, and service quality have a significant effect on customer loyalty. Abstrak. Tercapainya keberhasilan suatu perusahaan salah satunya adalah menciptakan loyalitas konsumen karena akan memberikan keuntungan kepada perusahaan dalam jangka waktu yang panjang. Hal tersebut juga ingin dicapai oleh Critoe Coffee yang pernah mengalami penurunan dan peningkatan penjualan di beberapa bulan, akibat penerapan price discount, store atmosphere dan service quality sehingga mempengaruhi jumlah konsumen yang rutin membeli atau konsumen yang loyal. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran price discount, store atmosphere, service quality dan costumer loyalty di Critoe Coffee Bandung serta untuk mengetahui pengaruh price discount, store atmosphere, service quality terhadap costumer loyalty. Penelitian ini merupakan jenis penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobability sampling yaitu purposive sampling. Populasi pada penelitian ini adalah konsumen yang sudah mengunjungi dan melakukan pembelian produk Critoe Coffee lebih dari dua kali dan didapatkan sampel sebanyak 396 orang. Analisis data yang digunakan adalah analisis deksriptif dan verifikatif menggunakan analisis regresi linier berganda, uji F, uji t, dan koefisien determinasi. Hasil penelitian ini menunjukkan bahwa price discount secara parsial berpengaruh signifikan terhadap costumer loyalty, store atmosphere secara parsial berpengaruh signifikan terhadap costumer loyalty dan service quality berpengaruh signifikan terhadap costumer loyalty. Lalu secara simultan price discount, store atmosphere, dan service quality berpengaruh signifikan terhadap costumer loyalty.